2022
DOI: 10.1002/ejp.2022
|View full text |Cite
|
Sign up to set email alerts
|

From protection to non‐protection: A mixed methods study investigating movement, posture and recovery from disabling low back pain

Abstract: Background Movement and posture are commonly believed to relate to low back pain (LBP). Yet, we know little about how people make sense of the relationship between their LBP, movement and posture, particularly after recovery. We aimed to qualitatively explore this understanding, how it changes and how it relates to quantitative changes. Methods A mixed method study in the context of an existing single‐case design involving 12 people with disabling non‐specific LBP. Interviews were conducted before and after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 122 publications
0
3
0
1
Order By: Relevance
“…As spinal amplitude is associated with psychological factors (Christe, Crombez, et al, 2021), interventions could notably improve spinal movement through reductions of unhelpful beliefs and pain‐related fear, which could at the same time decrease pain intensity (Christe et al, 2022). Similarly, reducing protective behaviours could reduce unhelpful beliefs and pain‐related fear (Caneiro et al, 2022; Wernli et al, 2022). Altogether, these findings support a biopsychosocial management of LBP, combining exercises and psychological interventions (Ho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As spinal amplitude is associated with psychological factors (Christe, Crombez, et al, 2021), interventions could notably improve spinal movement through reductions of unhelpful beliefs and pain‐related fear, which could at the same time decrease pain intensity (Christe et al, 2022). Similarly, reducing protective behaviours could reduce unhelpful beliefs and pain‐related fear (Caneiro et al, 2022; Wernli et al, 2022). Altogether, these findings support a biopsychosocial management of LBP, combining exercises and psychological interventions (Ho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested further investigation of “specific and personalized assessment of psychological variables, pain severity, and spinal motor behavior” ( Christe et al, 2021b ). Another study Wernli K et al (2022) demonstrated that each participant had an individual recovery journey from conscious and non-conscious protection to conscious and non-conscious non-protection. Prior to and following cognitive functional therapy intervention for 12 patients with disabling LBP, pre- and post-quantitative measures of movement, posture, psychological factors, pain, and activity limitation integrated well with the findings from qualitative interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Although causal inference cannot be made, this is indirectly supported by clinical evidence showing that decreased safety behaviour during activities (e.g. greater spinal range of motion, faster movement, more relaxed postures and less back muscle activity) is associated with less pain and experienced disability during those particular activities [70][71][72] .…”
Section: Theory Informing Practice To Help Eva Manage Her Back Painmentioning
confidence: 99%